2019
DOI: 10.3928/19404921-20190823-02
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Dementia Worry: Comparing Middle-Aged and Older Adults in South Korea

Abstract: As the number of individuals with dementia and exposure to dementia increases, worrying about dementia may threaten individuals' health and lifestyle. This cross-sectional study compared dementia worry and related factors between middle-aged and older adults in South Korea. A self-reported descriptive survey or face-to-face interview was conducted with 154 middle-aged adults (mean age = 55.8 years; 64.3% women) and 51 older adults (mean age = 71.3 years; 52.9% women) in South Korea. Older adults were more worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…This is an important finding, especially since stigmatic beliefs were found to be a deterrent to initiating health behaviors, such as help-seeking (Herrmann et al, 2018;Phillipson et al, 2015). However, while reducing stigma has been mentioned anecdotally as a potential way to manage dementia fear (Bowen et al, 2018;Ryu and Park, 2019;Scerri and Scerri, 2017), this association still awaits empirical examination.…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding, especially since stigmatic beliefs were found to be a deterrent to initiating health behaviors, such as help-seeking (Herrmann et al, 2018;Phillipson et al, 2015). However, while reducing stigma has been mentioned anecdotally as a potential way to manage dementia fear (Bowen et al, 2018;Ryu and Park, 2019;Scerri and Scerri, 2017), this association still awaits empirical examination.…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…First published online 13 Oct 2020 fear of perceiving normal cognitive changes as indications of dementia. Since then, the terms "dementia fear" (Cantegreil-Kallen and Pin, 2011;Ebert et al, 2019;Norman et al, 2019;Page et al, 2019), "dementia worry" (Fresson et al, 2017;Kessler et al, 2012;Kinzer and Suhr, 2016;Molden and Maxfield, 2016;Phillips et al, 2017;Ryu and Park, 2019;Wong et al, 2019), and "concerns about dementia" (Tang et al, 2017;Werner et al, 2013) have been used interchangeably, and almost exclusively to examine concerns about developing AD. Kessler and colleagues (2012) were the first to provide a clearer conceptualization of the construct by defining dementia fear as a multidimensional concept composed of cognitive (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…20,23,26,27 A lower level of education was significantly associated with dementia worry. 23,27,28 Dementia worry was higher in persons living alone 29 and in those belonging to a majority group 30 than in those living with others or in minority populations, respectively. Exposure to AD as a family member, caregiver, or acquaintance was associated with dementia worry in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…14,19,20 Studies on dementia worry found that dementia is a notably undesired diagnosis, second only to cancer. 21,22 Some studies on the relationship between dementia worry and participant age reported a positive association, 20,23 while another study reported a negative association. 19,24 Bowen et al 25 reported that dementia worry increased with age from 40 to 70 years and decreased after 70 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation